Patient-Reported Knee Function Versus Star Excursion Balance Performance as Correlates of Psychological Return-to-Sport Readiness After Anterior Cruciate Ligament Reconstruction - Ryan T. Halvorson; Aidan Foley; Hayden Sampson; Cameron Nosrat; Drew A. Lansdown; Brian T. Feeley; Jeannie F. Bailey (Bioengineering, 2026)
Background: Psychological readiness, quantified by the Anterior Cruciate Ligament Return to Sport after Injury (ACL-RSI) scale, is one of the most consistent correlates of return-to-sport success following ACL reconstruction. Whether psychological readiness reflects an independent construct or is related to measured functional performance is not known. Purpose: To evaluate the associations between patient-perceived knee function and objective performance on a functional task, as quantified by traditional scoring, kinematics, and motion quality, and psychological readiness 9 to 12 months after ACL reconstruction. Methods: In this cross-sectional study, forty patients performed the Star Excursion Balance Test using a validated markerless motion capture system. Three biomechanical domains derived from that task (reach distance, lower-extremity kinematics, and a time-series motion quality index) were evaluated against psychological readiness, with patient-reported function (as measured by the Knee Injury and Osteoarthritis Outcomes Score [KOOS-12]) as a comparator. Associations were estimated using multivariable regression adjusted for age, sex, body mass index, and limb length. Relative contributions were evaluated with variance decomposition, and Bayes factors quantified the strength of evidence for or against each association. Results: Patient-perceived knee function was strongly associated with psychological readiness (standardized β = 0.58; 95% confidence interval, 0.29 to 0.87; BF10 = 249), whereas no biomechanical domain derived from the functional task reached statistical significance (all |β| ≤ 0.34; all |r| ≤ 0.3). In the combined model (total R2 = 0.463), variance decomposition attributed 89.3% of explained variance in psychological readiness to patient-perceived knee function, versus 6.9% for reach distances, 2.4% for motion quality, and 1.4% for lower extremity kinematics. Bayes factors favored the null for each biomechanical domain, but reached only anecdotal strength (BF01, 1.3–2.8). Conclusion: In this cross-section, psychological readiness after ACL reconstruction more closely aligned with patient-perceived knee function than biomechanical performance on the SEBT, indicating that perceived function and biomechanical performance on certain tasks may be divergent at the time of return-to-sport clearance. These findings support the routine inclusion of patient-reported outcome measures alongside functional testing in multi-domain return-to-sport assessment.